Sintesis senyawa 2,4-Dihidroksiasetofenon dan Uji Aktivitasnya sebagai Antioksidan - Laksmiari Sekar Nirwani; Hery Muhamad Ansory; Anita Nilawati (Jurnal Farmasi Indonesia, 2018)
Antioxidant is very important to keep human’s health because of its capability to reduce freeradical. Acetophenone and its derivates are reported as potential antioxidant. The aim of thisresearch was to find antioxidant activity of 2,4-dihydroxyacetophenone compound synthesizedfrom resorcinol.The research was performed by synthesizing 2,4-dihydroxyacetophenon through Friedel-Crafts acylation from resorsinol. The structure of the compound was elucidated using gaschromatography, mass spectrometer, infrared spectrophotometer, and antioxidant test wasusing DPPH method.The results showed that product was succesfully synthesized. Yellowish-orange solid wasobtained from synthesis with 86,14% of yield and confirmed as 2,4-dihydroxyacetophenone.The product showed weak antioxidant activity with 36,72 ppm of IC50